A solvent-free headspace GC/MS method for sensitive screening of N-nitrosodimethylamine in drug products - Lee, Do Hee; Hwang, Su Hyeon; Park, Seoungchul; Lee, Jeongmi; Oh, Han Bin; Han, Sang Beom; Liu, Kwang-Hyun; Lee, Yong-Moon; Pyo, Hee Soo; Hong, Jongki (ROYAL SOC CHEMISTRY, 2021)
A solvent-free headspace gas chromatography-mass spectrometry (SF-HS-GC/MS) method was developed and validated for screening N-nitrosodimethylamine (NDMA) in various active pharmaceutical ingredients (APIs) and drug products. Experimental parameters such as incubation temperature, incubation time, and sample volume in solvent-free headspace conditions were optimized. The developed SF-HS-GC/MS method was validated in terms of linearity, limit of quantification (LOQ), precision, and accuracy. The results indicated excellent linearity from 5 to 500 ng g(-1) with correlation coefficients higher than 0.9999. The LOQ of this method was 5 ng g(-1) and matrix effects ranged from 0.97 to 1.11. The accuracy ranged from 92.77 to 106.54% and the precision RSDs were below 5.94%. No significant matrix effect was observed for any of the drug products. Also, artefactual NDMA formation in ranitidine, nizatidine, and metformin was investigated under HS conditions. Adjusted (mild) SF-HS conditions were suggested for precise quantification of NDMA in positive drug products by GC/MS. The present SF-HS-GC/MS method is a promising tool for the screening and determination of toxic NDMA in APIs and drug products.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; NITROSAMINES